Peran Father Involvement terhadap Self Esteem Remaja - Erna Risnawati; Fatma Nuraqmarina; Laila Meiliyandrie Indah Wardani (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2021)
The purpose of this study is to examine the role of fathers involvement in parenting towards the development of self esteem in adolescents. This research used quantitative method with purposive sampling technique. The participants were 149 adolescents who live with the their fathers. This study used self esteem scale by Rosenberg and father involvement scale which was developed by researcher based on the theory of Goncy and Van Dullman. The data analysis result using regression test shows that the contribution of the role of the father involvement on adolescent's self esteem is 38%, while the other 62% was caused by other factors. This finding indicate that the greater role of father in parenting, the higher self esteem. This study hopefully can increase father’s awareness and brings new pattern of family parenting about their roles that not only in economic but also for the psychological effect, especially self esteem.